Leadership Challenges in The Digital Era: Leadership Development Strategies for Man 2 Banyuwangi Principal in The Age of Technology - Lutfi Wakhid; Malikhatul Balqis (Universitas Negeri Malang, 2025)
Abstract: This study aims to formulate a principal's leadership strategy in the digital era with a focus on developing digital literacy, transforming school culture, and a collaborative approach. The study used a qualitative method with a case study approach with data collection methods through observation, interviews, and document analysis. Data were analyzed using the Miles and Huberman model through four stages, namely data collection, data reduction, data presentation, and drawing conclusions, with data validity guaranteed through triangulation. The results of the study indicate that digital literacy is a key competency that supports innovation, improves 21st century skills, and encourages institutional achievements such as the National Active Literacy School Champion 1 award. Principals play a role as agents of digital transformation through superior programs such as the Madrasah Literacy Movement (GELEM), the Joint Outdoor Literacy Movement (GLOBE), and the School Writing Book Movement (GSMB). Collaborative strategies involving teachers, students, and parents have been shown to accelerate technology adoption and create a harmonious work culture. However, challenges in the form of digital divides and infrastructure limitations need to be addressed through ongoing training and infrastructure strengthening. This study emphasizes the importance of visionary leadership, digital literacy, and collaboration to create a technology-based education ecosystem that is relevant in the digital era. Keywords: school principal leadership; digital literacy; digital transformation; collaborative approach